Aplicação de quimiometria e espectroscopia no infravermelho com transformada de Fourier e reflectância total atenuada na avaliação de canela (cinnamomum) orgânica - Bruni, Andressa Rafaella da Silva (2021)
Currently, the consumption of organic foods has increased considerably. Foods labeled organic should not contain residues of synthetic fertilizers, chemical pesticides, genetically modified organisms, hormones, and antibiotics. Among organic foods, cinnamon stands out for its characteristic flavor and bioactive compounds that are efficient in combating cancer, diabetes mellitus, oxidative stress, Alzheimer, Parkinson, among other diseases. One of the main concerns when dealing with organic foods is their identity, since the conventional techniques for this analysis are expensive, require time and sample preparation. Alternative methodologies based on simpler techniques, which have the benefits of low costs, quick execution, are nondestructive, without the need for sample preparation or the use of chemical reagents, are essential for this type of analysis. Thus, the work aimed to verify the potentials of Attenuated Total Reflectance Fourier Transform Mi- Infrared Spectroscopy (ATR-FT-MIR) coupled with Parallel Factor Analysis (PARAFAC) for evaluation of 10 commercial samples of powdered cinnamon (6 organic and non-organic). As a result, the proposal proved to be efficient for the evaluation of these cinnamon samples, differentiating them according to their class and verifying the variables for that reason, in with the spectral region above 2600 cm-1 was related to the distinction of organic samples, which corresponds to the absorption of CH, CH2, CH3, NH, NH2 and OH.